Communication skills: observation in civil society organizations in Salvador-Bahia-Brazil - Borges, Jussara (2013)
This paper is part of an attempt to understand the skills that are being requested and promoted by those who work in cyberspace. In this sense, the research does not intend to establish criteria and skills that people must possess, but to understand the expression of informational needs and the demands on communication skills of users/authors.